2019
DOI: 10.1016/j.cell.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Oncogene Rearrangements in the Mutational History of Lung Adenocarcinoma

Abstract: Highlights d Driver fusion oncogenes in LADCs are generated from complex genomic rearrangements d These rearrangements are frequently copy-number balanced, resembling germline events d Fusions often arise in early decades of life, leaving long latency to diagnosis d SETD2 inactivation is cooperative with fusion oncogenes in TP53-wild-type LADCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(167 citation statements)
references
References 69 publications
8
145
1
Order By: Relevance
“…1E, Table S1 (A companion study investigating Barrett's esophagus WGS dataset in detail is currently in preparation). In summary, our analysis included 1,668 WGS samples not currently within the Pan-Cancer Analysis of Whole Genomes (PCAWG) effort, including published studies (Nik-Zainal et al, 2016;Hayward et al, 2017;Baca et al, 2013;Lee et al, 2019;Barretina et al, 2012;Frankell et al, 2019), The Cancer Genome Atlas (TCGA, 1017 cases), International Cancer Genome Consortium (ICGC, 876 cases), or Cancer Cell Line Encyclopedia (CCLE, 326 cases) (Barretina et al, 2012;Ghandi et al, 2019). Though the majority of our analyzed samples consisted of primary tumors, 283 out of the 2,833 samples were extracted or derived from metastatic tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E, Table S1 (A companion study investigating Barrett's esophagus WGS dataset in detail is currently in preparation). In summary, our analysis included 1,668 WGS samples not currently within the Pan-Cancer Analysis of Whole Genomes (PCAWG) effort, including published studies (Nik-Zainal et al, 2016;Hayward et al, 2017;Baca et al, 2013;Lee et al, 2019;Barretina et al, 2012;Frankell et al, 2019), The Cancer Genome Atlas (TCGA, 1017 cases), International Cancer Genome Consortium (ICGC, 876 cases), or Cancer Cell Line Encyclopedia (CCLE, 326 cases) (Barretina et al, 2012;Ghandi et al, 2019). Though the majority of our analyzed samples consisted of primary tumors, 283 out of the 2,833 samples were extracted or derived from metastatic tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Criteria for inclusion into this 5 study were as follows: i) BAMs from only non-low pass WGS, ii) BAMs must be aligned to GRCh37/hg19, and iii) both 6 tumor and normal non-low pass WGS must exist per pair except for cell lines. Previously published WGS cohorts included in 7 this study were: 183 ICGC melanoma cases (Hayward et al, 2017), 49 ICGC lung adenocarcinomas (Lee et al, 2019), 122 8 ICGC breast cancers (Nik-Zainal et al, 2016), and 422 ICGC esoaphgeal adenocarcinomas (Frankell et al, 2019), 55 prostate 9 cancers (Baca et al, 2013), and also 326 unpaired CCLE cell lines (Barretina et al, 2012). Raw sequencing data was obtained 10 either from either public repositories with the proper permissions granted through dbGaP (for TCGA WGS BAMs) or through 11 the relevant Data Access Committees (for ICGC WGS BAMs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we also observed a similar signature by long-read sequencing of a renal cell carcinoma genome. Features of the TST jump signature have been described in large cancer data sets (1, 70) and tandem arrays of short insertions have also been noted in lung cancer genomes, where they may be common ((71) and J. Lee, personal communication). Although the cause of the TST jump signature is unknown, an origin for the insertions from Okazaki fragments might explain the size distribution of the insertions, which is strikingly similar in all of the contexts in which the pattern has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer arises through a process of somatic evolution and recent studies have shown that aneuploidies and driver gene mutations precede cancer diagnosis by several years to decades [1][2][3][4] Here, we address the question whether such genomic signals can be used for early detection and pre-emptive cancer treatment. To this end we study Barrett's oesophagus, a genomic copy number driven neoplastic precursor lesion to oesophageal adenocarcinoma 5 Cancer is caused by genetic mutations that lead to an uncontrolled proliferative and invasive cellular phenotype.…”
Section: Discussionmentioning
confidence: 99%